EXPERIMENTAL TESTING OF 3D PRINTED CONCRETE TRUSS GIRDER - Mitrović, Stefan; Vidović, Milica; Ignjatović, Ivan; Dragaš, Jelena (Journal of Applied Engineering Science, 2024)
In the last few decades, the technology of 3D concrete printing (3DCP) has had a significant development. This technology has a great potential to improve efficiency in the construction industry. It can provide safer site working conditions, material savings, a reduction of construction time, and a high versatility of architectural and structural design. However, this new technology is still not fully investigated. The wider application is limited by the lack of standards and guidelines for design and production. The literature review showed that, there are only a few studies investigating structural behaviour of 3DCP structures and elements. Beams and walls with and without addition of fibers, reinforcement or cables under ultimate loads were tested. The incorporation of reinforcement in the printing process, connections between printed pieces and long-term behaviour of 3DCP elements under sustained load are opened questions. The topic of this research was an experimental testing of 3DCP truss girder. Printing of truss girder was done using a commercial, ready-to-use premix Sikacrete® 751 3D. In order to print, the printer head was moved in the Z direction to alternately place two desired path layers. A truss girder with dimensions of 87x29x12 cm, without reinforcement, was subjected to a four-point bending test up to failure. During this testing strains in two diagonals, deflection of the two bottom joints, and ultimate force were measured. Ultimate force was 30 kN and the brittle failure of tensioned bottom chord occurred. The force in tensioned diagonal was 13.45 kN and in the compressed one 36.77 kN. Additionally, three samples obtained from the top and bottom chords were tested on axial tension. The tension capacity of samples was 25.12 kN.
Keywords: 3D printed concrete, experimental testing, truss girders, 4-point bending test